2009
DOI: 10.1051/0004-6361/200912046
|View full text |Cite
|
Sign up to set email alerts
|

Line broadening in the Si I, Si II, Si III, and Si IV spectra in the helium plasma

Abstract: Context. The neutral and ionized silicon spectral line shapes have been investigated in the laboratory helium plasma at electron densities ranging between 3.7 × 10 22 m −3 and 1.1 × 10 23 m −3 and electron temperatures between 12 500 K and 19 000 K, both interesting for astrophysics. Aims. The aim of this work is to present experimental Stark FWHM (full-width at half of the maximum line intensity, W) for number of spectral lines from neutral (Si I), singly (Si II), doubly (Si III), and triply (Si IV) ionized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Upward revision of log g would act in the same direction, however, the abundance shifts are smaller. For the majority of the Si ii lines in ι Her, we use the Γ 4 /N e values from laboratory measurements of Bukvić et al (2009). They are proven to work well for the stars (Sect.…”
Section: Uncertainties In Derived Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upward revision of log g would act in the same direction, however, the abundance shifts are smaller. For the majority of the Si ii lines in ι Her, we use the Γ 4 /N e values from laboratory measurements of Bukvić et al (2009). They are proven to work well for the stars (Sect.…”
Section: Uncertainties In Derived Abundancesmentioning
confidence: 99%
“…Bukvić et al (2009); 2 Wilke (2003, Ph.D. Thesis) as given by Fossati et al (2009); 3 VALD; 4 blend; 5 emission line. Ref.…”
mentioning
confidence: 99%
“…Satisfactory agreement was found. The Stark broadening of Si IV was calculated using our method in Elabidi et al [28] and comparisons with the experimental results of Bukvić et al [29] showed acceptable agreements. Extensive study of the influence of strong collisions on Stark broadening was performed in [30] for the calculations of Ar VII line widths.…”
Section: Introductionmentioning
confidence: 80%
“…Thus, the electron density was estimated relying on the known Stark FWHM of the 308.6 nm Si III (Bukvić et al 2009b) and the He II P α (468.6 nm) spectral line (Pittman & Fleurier 1986) within ±13% accuracy, connected to the He II P α FWHM. The 308.6 nm Si III line was chosen because it is intense, well isolated (see Fig.…”
Section: Methodsmentioning
confidence: 99%